The CME Acceleration Problem: Error Estimates in LASCO Coronal Mass Ejection Measurements - Wen, Yayuan; Maia, Dalmiro Jorge Filipe; Wang, Jingxiu (The Astrophysical journal, 2007)
The properties of the coronal mass ejections (CMEs) observed by the Large Angle and Spectrometric Coronagraph Experiment (LASCO) on the Solar and Heliospheric Observatory (SOHO) spacecraft are kept in an online catalog that has been widely used in a series of analyses of individual events and in statistical overviews of CME properties. A subject of some of these studies has been the problem of CME acceleration, in particular the differences between accelerated and decelerated events. The impact of measurement errors in the acceleration is an issue that has been mostly overlooked in such studies. We show in mis paper how to obtain error estimates for the height measurements given in the catalog of CMEs observed by LASCO. We find that the error in CME leading-edge position measurements grows rather quickly in the first few solar radii, roughly with the square of the distance from Sun center, but becomes reasonably flat above 5 R , varying approximately as the square root of the distance. Above 5 R the typical errors in acceleration are of the same order or larger than the accelerations computed from catalog data. Kinematic quantities computed above 5 R for individual events will mostly reflect the distribution of the errors in the acceleration, and not the true acceleration experienced by the events.